Analisis Pengaruh Inklusi Keuangan Syariah terhadap Indeks Pembangunan Manusia di Indonesia - Salma Nurul Zahara; Ruhadi Ruhadi; Setiawan Setiawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
Financial inclusion has an important role on the Human Development Index (HDI). This study aims to determine the value of Sharia Financial Inclusion from the value of each that dimension buldier and that effect on the HDI. The calculation uses the Index of Financial Inclusion method (Sarma and Pais, 2012) and panel data regression analysis to find that effect on HDI where the independent variable are the accessibility, availability and usage dimension and the dependent variable is Human Development Index (HDI). The period that used in this study is 2015-2019. The data used is secondary data from Otoritas Jasa Keuangan (OJK) and Badan Pusat Statistik (BPS). The result of this study show that each of dimensions buldier of Financial Inclusion have a low value. Simultaneously the variable accessibility dimension, availability dimension and usage dimension have an effect on Human Development Index. Meanwhile partially, the accessibility dimension has not an effect on HDI, availability dimension has a negative effect on HDI and usage dimension has a positive effect on HDI.